A stabilized assumed deformation gradient finite element formulation for strongly coupled poromechanical simulations at finite strain. (7th January 2013) - Sun, WaiChing; Ostien, Jakob T.; Salinger, Andrew G.
SUMMARY An adaptively stabilized finite element scheme is proposed for a strongly coupled hydro‐mechanical problem in fluid‐infiltrating porous solids at finite strain. We first present the derivation of the poromechanics model via mixture theory in large deformation. By exploiting assumed deformation gradient techniques, we develop a numerical procedure capable of simultaneously curing the multiple‐locking phenomena related to shear failure, incompressibility imposed by pore fluid, and/or incompressible solid skeleton and produce solutions that satisfy the inf‐sup condition. The template‐based generic programming and automatic differentiation (AD) techniques used to implement the stabilized model are also highlighted. Finally, numerical examples are given to show the versatility and efficiency of this model. Copyright © 2013 John Wiley & Sons, Ltd.